2010
DOI: 10.1111/j.1365-2435.2010.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the adaptive potential of critical thermal limits: methodological problems and evolutionary implications

Abstract: Summary1. Current studies indicate that estimates of thermal tolerance limits in ectotherms depend on the experimental protocol used, with slower and presumably more ecologically relevant rates of warming negatively affecting the upper thermal limits (CT max ). Recent empirical evidence also gives credence to earlier speculations suggesting that estimates of heritability could drop with slower heating rates. 2. Using published data from the fruit fly Drosophila melanogaster, we show that empirical patterns can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
349
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(367 citation statements)
references
References 65 publications
(138 reference statements)
10
349
5
3
Order By: Relevance
“…Nevertheless, in our opinion these confounding effects will be minor relative to heat resistance variation found between species. CT max as estimated in the present study may be confounded by effects of desiccation and starvation (assays are performed without food or moisture for ∼3 h) as discussed recently in the literature (43,44). This might inflate estimates of CT max particularly for highly desiccation/starvation-resistant species, but recent experiments on Drosophila melanogaster have found the impact of desiccation and starvation stress to be negligible with respect to CT max when using heat exposures similar to the one used here (45).…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, in our opinion these confounding effects will be minor relative to heat resistance variation found between species. CT max as estimated in the present study may be confounded by effects of desiccation and starvation (assays are performed without food or moisture for ∼3 h) as discussed recently in the literature (43,44). This might inflate estimates of CT max particularly for highly desiccation/starvation-resistant species, but recent experiments on Drosophila melanogaster have found the impact of desiccation and starvation stress to be negligible with respect to CT max when using heat exposures similar to the one used here (45).…”
Section: Discussionmentioning
confidence: 64%
“…Lower growth rates, poorer condition and higher mortality were reported for European sea bass, Dicentrarchus labrax (Vinagre et al, 2012a,b), higher mortality and lower growth rates were also reported for the Senegal sole, Solea senegalensis (Vinagre et al, 2013b) and higher mortality was reported for Senegal sea bream, Diplodus bellottii . Ultimately, the short-term temperature extremes that an organism can tolerate will depend on its phenotypic plasticity, but in the long run, evolutionary shifts in thermal limits will depend on the presence of additive genetic variance, with the selection of thermally tolerant genotypes over multiple generations being decisive (Rezende et al, 2011;Donelson et al, 2012). The crucial issue is whether the rate of evolutionary adaptation will be fast enough to keep up with the rate of environmental warming (Stockwell et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…0.1 vs 0.06°Cmin -1 ) (Mora and Maya, 2006;Terblanche et al, 2007;Chown et al, 2009;Overgaard et al, 2012). Rezende et al (Rezende et al, 2011) commented on this observation and stated that it is '...a puzzling result because slower heating rates should allow individuals to acclimatize to new temperatures and because slow heating pre-exposes individuals to non-lethal high temperatures ('hardening'), which increases heat shock resistance (see e.g. Hoffmann et al, 2003)'.…”
Section: Introductionmentioning
confidence: 99%